Aspects of intellectual capital evaluation - Stankevičienė, Asta; Liučvaitienė, Aušra (Business: Theory and Practice, 2012)
This article analyses possible aspects of intellectual capital evaluation in Lithuanian companies. The first part of the article presents interpretation of the definition of an intellectual capital. The latter concept is analysed according to its description basis and possible control methods.Also, it presents the structure of intellectual capital disclosing the main aspects of intellectual capital evaluation. In the second part notably great attention is paid to the intellectual capital evaluation aspects identifying main problems and presenting possible ways for their solution. By presenting general intellectual capital measuring and evaluation models and indices, it is aimed to apply the latter for evaluation of the intellectual capital of Lithuanian companies. While carrying out the research, the data of questionnaire inquiry, expert (ranging of indices of intellectual capital) evaluation and multi-criteria method were referred to. The results of the research have revealed that the index of the intellectual capital in the investigated small (9 employees) and medium (90 employees) companies differs. The received rate value in the small company equals to 0.398, i.e. low evaluation and respectively in the medium company it is 0.704, i.e. medium evaluation. In such case it can be stated that the result of intellectual capital evaluation is conditioned by the size of the company, its activity and view of the managers themselves on the demand for intellectual capital measuring. Expedience of intellectual capital measuring and evaluation could be determined by the attitude that the latter is directly related to acquiring and maintaining the competitive advantage. Article in Lithuanian. Intelektinio kapitalo vertinimo aspektai Santrauka. Šiame straipsnyje analizuojami galimi intelektinio kapitalo vertinimo aspektai Lietuvos įmonėse. Pirmoje straipsnio dalyje pateikiama intelektinio kapitalo definicijos interpretacija. Ši sąvoka analizuojama pagal jos apibūdinimo pagrindą ir galimus valdymo būdus. Taip pat pateikiama intelektinio kapitalo struktūra, atskleidžiant pagrindinius intelektinio kapitalo vertinimo aspektus. Antroje dalyje itin daug dėmesio skiriama intelektinio kapitalo vertinimo aspektams, identifikuojant pagrindines problemas ir pateikiant galimus jų sprendimo būdus. Pateikiant bendrus intelektinio kapitalo matavimo ir vertinimo modelius bei rodiklius, siekiama juos pritaikyti Lietuvos įmonių intelektiniam kapitalui vertinti. Atliekant tyrimą remtasi anketinės apklausos duomenimis, ekspertiniu (intelektinio kapitalo rodiklių rangavimo) vertinimo metodu. Tyrimo rezultatai parodė, kad intelektinio kapitalo indeksas tirtose mažoje (dirba 9 darbuotojai) ir vidutinėje (dirba 90 darbuotojų) įmonėse skiriasi. Mažoje įmonėje gauta koeficiento reikšmė lygi 0,398, t. y. žemas vertinimas, atitinkamai vidutinėje įmonėje – 0,704, t. y. vidutinis vertinimas. Tokiu atveju galima teigti, kad intelektinio kapitalo vertinimo rezultatą lemia įmonės dydis, veiklos pobūdis bei pačių vadovų požiūris į intelektinio kapitalo matavimo poreikį. Intelektinio kapitalo matavimo ir vertinimo tikslingumą galėtų lemti nuostata, kad jis tiesiogiai susijęs su konkurencinio pranašumo įgijimu ir išlaikymu. Reikšminiai žodžiai: kapitalas, intelektinis kapitalas, nematerialusis turtas, intelektinio kapitalo struktūra, intelektinio kapitalo matavimo rodikliai, intelektinio kapitalo vertinimo schema.